Gangguan Kognitif Pasca Cedera Otak Traumatik - Janet Loprang; Christopher Lampah; Lidwina Sengkey (UNIVERSITAS SAM RATULANGI, 2022)
Abstract: Traumatic brain injury is an increasing public health problem and is a significant cause of morbidity and mortality worldwide. Every year around 10 million people experience traumatic brain injuries worldwide. According to Riskesdas 2018, the prevalence of traumatic brain injury in Indonesia is 11.9%. A global report on driving safety by the World Health Organization in 2013 demonstrated the magnitude of this problem now and in the future throughout the world, and the need for well-developed and evaluated programs for prevention, management and rehabilitation. Of the 2 million people experiencing traumatic brain injury, around 1 million require rehabilitation services at the national level. People with traumatic brain injuries can experience chronic disabilities that impact a person's life in terms of cognitive, behavioral, psychosocial, physical, and vocational issues. Cognitive impairment is the most disruptive disorder for people with traumatic brain injury, family members, and the community. Cognitive deficits can significantly affect activities of daily living (ADL), work, social relationships, recreation, and active participation in the community. Traumatic brain injuries are classified as mild, moderate, and severe based on the level of consciousness, especially the duration of post-traumatic coma and amnesia Keywords: Traumatic; Brain; Injury; Cognitive Abstrak: Cedera otak traumatik adalah masalah kesehatan publik yang semakin meningkat dan merupakan salah satu penyebab morbiditas dan mortalitas yang signifikan di dunia. Setiap tahunnya sekitar 10 juta orang mengalami cedera otak traumatik di seluruh dunia. Menurut Riskesdas 2018, prevalensi kejadian cedera otak traumatik di Indonesia berada pada angka 11,9%. Sebuah laporan global mengenai keselamatan berkendara oleh World Health Organization tahun 2013 menunjukkan besarnya masalah ini sekarang dan pada masa yang akan datang di seluruh dunia, dan dibutuhkannya program yang dibuat dan dievaluasi secara baik untuk pencegahan, tatalaksana, dan rehabilitasi. Dari 2 juta orang mengalami cedera otak traumatik, sekitar 1 juta membutuhkan pelayanan rehabilitasi pada tingkat nasional. Orang-orang dengan cedera otak traumatik dapat mengalami disabilitas kronis yang berdampak pada kehidupan seseorang dalam hal kognitif, perilaku, psikososial, fisik, dan masalah vokasional. Gangguan kognitif adalah gangguan yang paling mengganggu bagi orang yang mengalami cedera otak traumatik, anggota keluarga, dan bagi komunitas. Defisit kognitif dapat memengaruhi activities of daily living (ADL), pekerjaan, hubungan sosial, rekreasi, dan partisipasi aktif dalam komunitas secara signifikan. Cedera otak traumatik diklasifikasikan sebagai ringan, sedang, dan berat berdasarkan tingkat kesadaran, terutama durasi koma dan amnesia pasca trauma Kata Kunci: Traumatik; Otak; Cedera; Kognitif